The status of insurance as an alternative to aqilah for diyat payments pertaining to road accidents. - Ahmad Muhammad Husni,; Anwar Fakhri Omar,; Muhammad Nazir Alias,; Muhammad al-Adib Samuri, (Institut Kajian Rantau Asia Barat, 2012)
In some Islamic countries, traffic accidents are categorised as unintentional harm or fatality cases. The laws of these countries allow for the aggrieved party to demand diyat (compensation for the loss suffered) from the offender that may be paid by their aqilah (in its original context, means community or tribe), or male family members. The question that then arises is to what extent can the aqilah be replaced by insurance agencies as the payer of diyat to the victim(s) or their respected families? The objective of this article is to determine this extent, specifically with regards to traffic accidents. This is an issue of great significance because insurance agencies are better equipped and more effective at providing coverage and protection to their policyholders, and as such have the potential to replace the aqilah system in situations where the financial means for such a payment is not present. Studies have shown that insurance agencies do indeed possess the potential to replace the aqilah system in the capacity of diyat compensation to victim(s) or their families, especially in the case of road accidents. It should be pointed out that insurance agencies possess inherent similarities to the aqilah system, particularly in relation to its basic concept, role and execution in achieving the same goals.